Brain drain and international migration of scientists: The case of Greece - Kourvetraris, George A. (The Greek Review of Social Research, 1973)
Tn this paper an effort was made to dispassionately examine the Greek «brain drain» within the context of international migration of scientists. Brain drain was analyzed as a symptom and as an aspect of the Greek social structure and the problem of Greek migration in general. Certain conceptual/theoretical and empirical aspects of «brain drain» controversy as they impinge upon particular countries including Greece were explored. Indeed, the purpose of the paper was primarily exploratory and diagnostic and only secondarily therapeutic and ameliorative in nature. Regarding the latter an agenda of interconnected specific and general recommendations were offered as pedagogical and policy guidelines. These guidelines, however, should not be construed as the only alternatives in bringing about change in Greece. It is the opinion of this author that whatever changes should be initiated should first spring from within the Greek social structure. A rational long range plan grounded in past, present, and future realities and potentialities of Greek brain power should be initiated vis-a-vis the needs and prospects for the national development of the Greek nation within the European and Middle-Eastern community of nations. In planning her future development, Greece can benefit and capitalize from Greek scientists in the diaspora without necessarily committing herself to a policy of their repatriation. Indeed, it seems to this writer that Greek «brain drain» can be transformed to a «brain drain» and/or «brain exchange» if the national and educational leadership in Greece adopt a cosmopolitan posture regarding science and encourage both Greek scientists in Greece proper and those Greek and non-Greek scientists overseas who are interested to carry out individual or joint research and teaching in Greece.